The development and validation of a disordered eating screening tool for current and former athletes: The Athletic Disordered Eating (ADE) screening tool - Buckley G. L.; Lassemillante, A.-C. M.; Cooke, M. B.; Belski, R. (Nutrients, 2024)
Background: Current and former athletes are one of the most at-risk population groups for disordered eating (DE), impacting their dietary practices, body composition, performance and health during and following their athletic careers. Few comprehensive DE screening tools exist for this group. To help address this, the current study utilised a mixed-methods approach of Classic Test Theory (CTT) and Item Response Theory (IRT) to develop and validate a DE screening tool suitable for current and former athletes.